The hidden side of scalar-triplet models with spontaneous CP violation - Ferreira, Pedro Miguel (2022)
Scalar triplet extensions of the Standard Model provide an interesting playground for the explanation of neutrino mass suppression through the type-II seesaw mechanism. Propelled by the possible connections with leptonic CP violation, we explore under which conditions spontaneous CP violation can arise in models with extra scalar triplets. The minimal model satisfying such conditions requires adding two such triplets to the SM field content. For this model, the scalar mass spectrum in both the CP-conserving and spontaneous CP-violating scenarios is studied. In the former case, a decoupling limit for the new scalars can be achieved, while this is not the case when CP is spontaneously broken. In particular, we show that the existence of two light neutral scalars with masses below a few tenths of GeVs is unavoidable in the CP-violating case. Using matrix theory theorems, we derive upper bounds for the masses of those light scalars and briefly examine whether they can still be experimentally viable. Other interesting features of the scalar mass spectrum are discussed as, e.g., the existence of relations among the charged and neutral scalar masses.